Precarious life: The powers of mourning and violence - Butler, Judith (Verso, 2004)
Responding to the US’s perpetual war, Butler explores how mourning could inspire solidarity.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; corps; discipline; guerre; histoire et politique; médias; philosophie; périodes historiques; régions géographiques; sciences humaines; thématiques; violences; états-unis; éthique

No future: Queer theory and the death drive - Edelman, Lee (Duke University Press., 2004)
In this searing polemic, Lee Edelman outlines a radically uncompromising new ethics of queer theory. His main target is the all-pervasive figure of the child, which he reads as the linchpin of our universal politics of “reproductive futurism.” Edelman argues that the child, understood as innocence in need of protection, represents the possibility of the future against which the queer is positioned as the embodiment of a relentlessly narcissistic, antisocial, and future-negating drive. He boldly insists that the efficacy of queerness lies in its very willingness to embrace this refusal of the social and political order. In No Future, Edelman urges queers to abandon the stance of accommodation and accede to their status as figures for the force of a negativity that he links with irony, jouissance, and, ultimately, the death drive itself. Closely engaging with literary texts, Edelman makes a compelling case for imagining Scrooge without Tiny Tim and Silas Marner without little Eppie. Looking to Alfred Hitchcock’s films, he embraces two of the director’s most notorious creations: the sadistic Leonard of North by Northwest, who steps on the hand that holds the couple precariously above the abyss, and the terrifying title figures of The Birds, with their predilection for children. Edelman enlarges the reach of contemporary psychoanalytic theory as he brings it to bear not only on works of literature and film but also on such current political flashpoints as gay marriage and gay parenting. Throwing down the theoretical gauntlet, No Future reimagines queerness with a passion certain to spark an equally impassioned debate among its readers
Keywords: amériques; approches et analyses; cinéma; communication; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; premier cycle; psychanalyse; queer; régions géographiques; sciences humaines; thématiques; violences; états-unis; études culturelles

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (University of Minnesota Press, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

The impact of culture and minority status on women's experience of domestic violence - Kasturirangan, Aarati; Krishnan, Sandhya; Riger, Stephanie (Trauma, violence & abuse, 2004)
The influence of culture and ethnic background on women’s experience of domestic violence has been explored in research only recently. Here the authors review research about the impact of culture and minority status in the United States on women’s experience of domestic violence, considering family structure,immigration, acculturation, oppression, and community response. The authors encourage researchers and service providers to acknowledge the effects on women of sociopolitical dynamics, including racism, and to identify specific aspects of culture that are relevant to intimate partner abuse.
Keywords: amériques; approches et analyses; cours; discipline; intersectionnalité; justice sociale; pauvreté; premier cycle; psychologie; racisme; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

La haine et l'amour, la boîte noire du féminisme? Une critique de l'éthique du dévouement - Molinier, Pascale (Nouvelles Questions Feministes, 2004)
Les soins étant réalisés majoritairement par des femmes, on tend à considérer l’amour (des malades, des enfants) « naturel » et normal. Or, le travail de soin peut également générer de la haine envers les personnes dépendantes. Celle-ci n’est pas moins normale que l’amour et sa prise en compte modifie l’analyse des situations de soins. Pour l’heure, la haine est occultée dans les traditions savantes, en particulier dans les théories de l’éthique du dévouement, comme dans les témoignages des travailleuses, ainsi que le suggère une enquête réalisée auprès d’auxiliaires de puériculture. Il en résulte un déficit de visibilité du travail qui permet de conjurer la haine et la violence
Keywords: approches et analyses; care; discipline; discours dominant; projet charge mentale; psychologie; ressource en ligne; sciences humaines; sexisme; soins aux enfants; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences